Floral parts of Gomphrena globosa L. as a novel alternative source of betacyanins: Optimization of the extraction using response surface methodology - Roriz, Custódio Lobo (2018)
The present study describes a novel mechanical process for the pigmented parts of Gomphrena globosa L. The effects of the variables of the maceration extraction of betacyanins have not been properly described. Therefore, this study also aims to optimize the conditions that maximize betacyanins extraction from G. globosa as an alternative source. Assisted by response surface methodology, an experimental design was developed for testing the extraction variables (time, temperature, ethanol-water proportion and solid-liquid ratio). The responses used were betacyanins quantification (by HPLC-PDA-MS/ESI and spectrophotometric analysis), the extraction-yield and the colour intensity of the produced powder. The betacyanins identified were gomphrenin and isogomphrenin II and III. The highest betacyanins content ( 45 mg/g) was obtained by 165 min, 25 C, 0% of ethanol and 5 g/L of solid-liquid ratio. The betacyanins content from the floral parts of G. globosa is higher than those normally found in other sources highlighting its industrial application.